Preparation method of nitrogen-sulfur co-doped fluorescent carbon quantum dots with high quantum yield

By using a combination method of nitrogen and sulfur co-doping and eutectic solvents in carbon quantum dots, the problems of low quantum yield and poor graphitization structure in the prior art are solved, and high quantum yield and The preparation of nitrogen-sulphur co-doped carbon quantum dots with high graphitization has excellent photoluminescence and structural order.

CN119306210APending Publication Date: 2025-01-14QINGDAO UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411473180.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

In the prior art, heteroatom-doped lignin-based carbon quantum dots have low quantum yields and poor order of graphitization structures, which cannot meet the needs of high quantum yields and high graphitization degrees.

Method used

Sodium lignin sulfonate dissolved in a low-melt solvent composed of choline chloride and p-toluenesulfonic acid, and the reaction is heated to generate fluorescent carbon quantum dots co-doped with nitrogen and sulfur, which improves the quantum yield through the coordinated doping of nitrogen and sulfur. , and high content of N and S atoms are formed through hydrogen bonding in the eutectic solvent, changing the structure and electronic structure of carbon quantum dots.

Benefits of technology

The high quantum yield has been improved, the quantum yield of carbon quantum dots reaches 56%, and has a highly ordered graphitized structure and good photoluminescence, with adjustable particle size.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306210A_ABST
    Figure CN119306210A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation of carbon quantum dots, and discloses a preparation method of nitrogen-sulfur co-doped fluorescent carbon quantum dots with high quantum yield. The preparation method comprises the following steps: dissolving sodium lignin sulfonate in a deep eutectic solvent composed of choline chloride ChCl and p-toluenesulfonic acid PTA, carrying out a heating reaction, and after the reaction is finished, generating nitrogen-sulfur co-doped fluorescent carbon quantum dots N, S-CQDs; the deep eutectic solvent composed of the choline chloride ChCl and the p-toluenesulfonic acid PTA is a deep eutectic solvent ChCl / PTA composed of the choline chloride ChCl and the p-toluenesulfonic acid PTA in a molar ratio of 1: 1. The nitrogen-sulfur co-doped fluorescent carbon quantum dot with high quantum yield prepared by the preparation method provided by the invention has the quantum yield of 56% or more, the fluorescence intensity is the best under ultraviolet irradiation, and the carbon quantum dot has a highly ordered graphitized structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon quantum dot preparation, and in particular relates to a method for preparing nitrogen-sulfur co-doped fluorescent carbon quantum dots with high quantum yield. Background Art

[0002] Carbon quantum dots (COQs) are a type of quasi-spherical fluorescent nanomaterial with a size of less than 10 nm. Compared with traditional carbon materials and semiconductor materials, they have good fluorescence stability and can be used in fields such as light-emitting diodes. In addition, carbon quantum dots have good biocompatibility and low toxicity, and can be used as green probes in biological imaging and sensing and drug delivery.

[0003] Biomass materials have become a hot spot for the preparation of carbon quantum dots. Lignin mainly includes alkali lignin, lignin sulfonate, and lignin sulfate. Lignin is the only aromatic compound in nature, with the advantages of rich content, biodegradability, good thermal stability, etc., and has great application potential. The basic structural units of lignin include p-hydroxyphenyl, guaiacyl, and syringyl. The annual production of lignin can reach millions of tons, and its preparation method has caused great waste of resources and environmental pollution. Lignin is an ideal precursor material for the preparation of carbon quantum dots; lignin also has a rich aromatic structure, which can ensure the formation of the main carbon skeleton structure during the nucleation process of carbon quantum dots; the rich O-containing functional groups in lignin also create conditions for the formation of rich surface defects in carbon quantum dots and provide heteroatom doping sites, which is conducive to the regulation of the fluorescence properties and emission wavelength of carbon quantum dots. However, the preparation of carbon quantum dots from heteroatom-doped lignin still has the pain points of low quantum yield and poor order of graphitization structure, which cannot meet the requirements of nitrogen-sulfur co-doped carbon quantum dots in terms of high quantum yield and high degree of graphitization. Summary of the invention

[0004] In order to solve the problems of low quantum yield and poor orderliness of graphitized structure of heteroatom-doped lignin-based carbon quantum dots in the prior art, the present invention provides a method for preparing nitrogen-sulfur co-doped fluorescent carbon quantum dots with high quantum yield.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0006] The invention discloses a method for preparing nitrogen-sulfur co-doped fluorescent carbon quantum dots with high quantum yield, comprising dissolving sodium lignin sulfonate in a low eutectic solvent composed of choline chloride (ChCl) and p-toluenesulfonic acid (PTA), heating the mixture for reaction, and generating nitrogen-sulfur co-doped fluorescent carbon quantum dots (N,S-CQDs) after the reaction is completed; the low eutectic solvent composed of choline chloride (ChCl) and p-toluenesulfonic acid (PTA) is a low eutectic solvent composed of choline chloride (ChCl) and p-toluenesulfonic acid (PTA) with a molar ratio of 1:1.

[0007] Furthermore, the deep eutectic solvent contains 20% (m / v) sodium lignin sulfonate.

[0008] Furthermore, the heating reaction time is 14 hours, and the heating reaction temperature is 200°C.

[0009] Furthermore, after the reaction of the present invention is completed, the reaction solution is cooled, and then the reaction solution is filtered, the filtrate is dialyzed, and finally the liquid in the dialysis bag is freeze-dried.

[0010] Furthermore, the filtration is performed using a 0.22 μm filter membrane; the filtrate is dialyzed in a dialysis bag for 48 hours, and the molecular weight cutoff of the dialysis bag is 1000.

[0011] The preparation method of the low eutectic solvent ChCl / PTA of the present invention is: mixing a hydrogen bond acceptor choline chloride ChCl and a hydrogen bond donor p-toluenesulfonic acid PTA in a molar ratio of 1:1, heating and stirring after mixing evenly to a clear and transparent liquid, and then cooling to room temperature to obtain a low eutectic solvent, which is recorded as ChCl / PTA.

[0012] Finally, the present invention also provides nitrogen-sulfur co-doped fluorescent carbon quantum dots N,S-CQDs prepared by the above preparation method.

[0013] The present invention dissolves sodium lignin sulfonate in a low eutectic solvent composed of choline chloride ChCl and p-toluenesulfonic acid PTA, and heats the reaction to synthesize high quantum yield high nitrogen and sulfur co-doped fluorescent carbon quantum dots N, S-CQDs. Compared with the prior art, the nitrogen and sulfur co-doped fluorescent carbon quantum dots N, S-CQDs prepared by the preparation method provided by the present invention have the following beneficial effects:

[0014] The low eutectic solvent composed of choline chloride ChCl and p-toluenesulfonic acid PTA provided by the present invention, choline chloride (C5H 14 ClNO) contains nitrogen and can be used as a nitrogen dopant to introduce nitrogen. Sodium lignin sulfonate (C 20 H 24 Na2O 10S2) and p-toluenesulfonic acid (C6H6O3S) both contain sulfur. Thiophene and sulfone sulfur elements are successfully doped into the framework and edge functional groups of carbon quantum dots. High-content N and S synergistic doping is the key to achieving high quantum yield, especially high-content S forms bonds in the framework of GQD, which increases the quantum yield of carbon quantum dots; low eutectic solvent ChCl / PTA makes carbon quantum dots have a high sulfur content, so that carbon dots have more defects, thereby changing the structure and energy level, and further improving the quantum yield of carbon dots; high-content N and S atom doping changes the electronic structure of carbon quantum dots, increases the conjugation degree and electron density of carbon quantum dots, and also contributes to the improvement of the quantum yield of carbon quantum dots. The experimental results show that the quantum yield of nitrogen-sulfur co-doped fluorescent carbon quantum dots obtained by the preparation method provided by the present invention is unexpectedly high at 56%.

[0015] Secondly, the nitrogen-sulfur co-doped fluorescent carbon quantum dots prepared by the present invention have good photoluminescence and highly ordered graphitized structure. The test results show that the nitrogen-sulfur co-doped fluorescent carbon quantum dots prepared by the present invention have the best fluorescence intensity under ultraviolet light irradiation, and the IG / ID of the carbon quantum dots prepared by the present invention using the low eutectic solvent ChCl / 3PTA is 1.42, indicating that the carbon quantum dots ChCl / 3PTA have a highly ordered graphitized structure, which can achieve the increase of particle size and the adjustable red-shift emission. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 TEM and HR-TEM (upper right corner) images of five nitrogen-sulfur doped carbon quantum dots;

[0017] Figure 2 FT-IR spectra of five nitrogen-sulfur doped carbon quantum dots, where a is CQDs-WAT-200, b is CQDs-FOA-200, c is CQDs-LAA-200, d is CQDs-PRA-200, and e is CQDs-PTA-200;

[0018] Figure 3(a) is the full XPS spectra of five nitrogen-sulfur doped carbon quantum dots, and Figure 3(b) is the detailed spectra of five nitrogen-sulfur doped carbon quantum dots d, where a is CQDs-WAT-200, b is CQDs-FOA-200, c is CQDs-LAA-200, d is CQDs-PRA-200, and e is CQDs-PTA-200;

[0019] Figure 4UV-visible absorption spectra of five nitrogen-sulfur doped carbon quantum dots, where a is CQDs-WAT-200, b is CQDs-FOA-200, c is CQDs-LAA-200, d is CQDs-PRA-200, and e is CQDs-PTA-200;

[0020] Figure 5 Fluorescence spectra of five nitrogen-sulfur doped carbon quantum dots, where a is CQDs-WAT-200, b is CQDs-FOA-200, c is CQDs-LAA-200, d is CQDs-PRA-200, and e is CQDs-PTA-200;

[0021] Figure 6 These are the Raman spectra of five nitrogen-sulfur doped carbon quantum dots, where a is CQDs-WAT-200, b is CQDs-FOA-200, c is CQDs-LAA-200, d is CQDs-PRA-200, and e is CQDs-PTA-200. DETAILED DESCRIPTION

[0022] The present invention discloses a method for preparing nitrogen-sulfur co-doped fluorescent carbon quantum dots with high quantum yield. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.

[0023] In order to enable those skilled in the art to better understand the present invention, the present invention is further described in detail below in conjunction with specific implementation methods.

[0024] The calculation method and formula of quantum yield described in the present invention are as follows:

[0025] 0.1M quinine sulfate is used as a reference to calculate the relative quantum yield of the carbon quantum dot solution. The quantum yield of quinine sulfate at an excitation wavelength of 360nm is 54%. The specific test steps are as follows: first, an ultraviolet absorption spectrum test is performed to keep the absorbance of the prepared carbon quantum dot solution and quinine sulfate at around 0.05, and then the integral area of ​​the fluorescence peak is obtained by measuring the fluorescence emission spectrum. Both the ultraviolet spectrum and the fluorescence spectrum are measured at a wavelength of 280nm / 270nm. The calculation formula for the quantum yield of carbon quantum dots is as follows:

[0026]

[0027] In the formula, Q represents the fluorescence quantum yield, 1 is the integrated area of ​​the fluorescence peak, A is the absorbance of the solution at 280nm / 270nm, ω refers to the refractive index of the solvent, and S refers to the quinine sulfate reference solution.

[0028] Comparative Example 1 Preparation of Carbon Quantum Dots by Hydrothermal Method

[0029] 0.5 g of sodium lignin sulfonate was dissolved in 25 ml of water and placed in a high-pressure reactor. The reaction was carried out in a homogeneous reactor at 200° C. for 14 hours. After the reactor was cooled to room temperature, the reaction solution was filtered with a 0.22 μm filter membrane, and the filtrate was dialyzed with a dialysis bag for 48 hours. After the dialysis was completed, the liquid in the bag was freeze-dried for 48 hours to obtain sodium lignin sulfonate-based nitrogen and sulfur element-doped carbon quantum dots, recorded as CQDs-WAT-200. After calculation, the quantum yield of the carbon quantum dots obtained in this comparative example was 11.62%.

[0030] Comparative Example 2 Preparation of Nitrogen-Sulfur Doped Carbon Quantum Dots with Low Quantum Yield

[0031] 0.5 g of sodium lignin sulfonate was dissolved in 25 ml of ChCl / 3FOA, ChCl / 3LAA, and ChCl / 3PRA low eutectic solvents, respectively, and placed in a high-pressure reactor. The reaction was carried out in a homogeneous reactor at 200°C for 14 hours. After the reactor was cooled to room temperature, the reaction solution was filtered with a 0.22 μm filter membrane, and the filtrate was dialyzed with a dialysis bag for 48 hours. After the dialysis was completed, the liquid in the bag was freeze-dried for 48 hours to obtain sodium lignin sulfonate-based nitrogen and sulfur element-doped carbon quantum dots, which were respectively recorded as CQDs-FOA-200, CQDs-LAA-200, CQDs-PRA-200, and CQDs-PTA-200. After calculation, the quantum yields of the carbon quantum dots obtained in this comparative example were 28.58%, 21.90%, and 19.58%, respectively.

[0032] Example 1 Preparation of deep eutectic solvent

[0033] Choline chloride (ChCl) is used as a hydrogen bond acceptor, formic acid (FOA), lactic acid (LAA), malonic acid (PRA), and p-toluenesulfonic acid (PTA) are used as hydrogen bond donors, choline chloride (ChCl) and formic acid (FOA), lactic acid LAA), malonic acid (PRA), and p-toluenesulfonic acid (PTA) are mixed in a molar ratio of 1:3, 1:3, 1:3, and 1:1, respectively, and after mixing evenly, heated and stirred at 80°C and 400r / min until a clear and transparent liquid is obtained, and then cooled to room temperature, and finally four low eutectic solvents are obtained, which are respectively recorded as ChCl / 3FOA, ChCl / 3LAA, ChCl / 3PRA, and ChCl / PTA. The low eutectic solvents ChCl / 3FOA, ChCl / 3LAA, and ChCl / 3PRA used in Comparative Example 2 of the present invention are prepared by the preparation method of the low eutectic solvent of this embodiment, and the ChCl / PTA used in Example 2 of the present invention is also prepared by the preparation method of the low eutectic solvent of this embodiment.

[0034] Example 2 Preparation of high quantum yield nitrogen-sulfur co-doped fluorescent carbon quantum dots

[0035] 0.5 g of sodium lignin sulfonate was dissolved in 25 ml of ChCl / PTA low eutectic solvent system and placed in a high-pressure reactor. The reaction was carried out in a homogeneous reactor at 200° C. for 14 h. After the reactor was cooled to room temperature, the reaction solution was filtered with a 0.22 μm filter membrane, and the filtrate was dialyzed with a dialysis bag for 48 h. After the dialysis was completed, the liquid in the bag was freeze-dried for 48 h to obtain sodium lignin sulfonate-based nitrogen and sulfur element-doped carbon quantum dots, recorded as CQDs-PTA-200. After calculation, the quantum yield of the carbon quantum dots obtained in this embodiment was 56%.

[0036] The data analysis of the comparative examples and the examples shows that the quantum yield of the carbon quantum dots prepared by the low eutectic solvent system is improved compared to the carbon quantum dots prepared by the traditional hydrothermal method. Both Example 2 and Comparative Example 2 use different types of low eutectic solvents to participate in the preparation of nitrogen and sulfur element-doped carbon quantum dots. The quantum yield of the carbon quantum dots prepared by the low eutectic solvent ChCl / PTA in Example 2 of the present invention is as high as 56%, which is significantly and unexpectedly higher than the carbon quantum dots prepared by the low eutectic solvent in the comparative example. Compared with the traditional hydrothermal method for preparing carbon quantum dots, its quantum yield is about five times higher; the quantum yield of carbon quantum dots prepared by different types of low eutectic solvent systems is different, which may be due to the different hydrogen bonding effects of different low eutectic solvents, the stability of hydrogen bonds formed, and their own structures.

[0037] Effect Example

[0038] The synthesis of N,S-CQDs from sodium lignin sulfonate mainly involves molecular depolymerization and repolymerization. Under high temperature and high pressure conditions, sodium lignin sulfonate will be hydrolyzed into various small molecules (phenols, aromatic ethers, aromatic acids, etc.), and then dehydrated, polymerized, cycloaddition and other reactions will occur under the action of acidic low eutectic solvents to form heteroatom compounds, and finally carbonized, aromatized and further nucleated to form CQDs.

[0039] 3.1 The morphology of the sodium lignin sulfonate-based nitrogen and sulfur-doped carbon quantum dots obtained in Example 2, Comparative Example 1 and Comparative Example 2 is shown in Figure 1 ,It can be seen from the TEM images that the lattice fringes of the five CQDs are all around 0.21nm, corresponding to graphite carbon (100), indicating that the prepared CQDs all have a highly crystalline graphite carbon structure.

[0040] 3.2 Comparative Examples and Examples The element contents of the carbon quantum dots CQDs-WAT-200, CQDs-FOA-200, CQDs-LAA-200, CQDs-PRA-200 and CQDs-PTA-200 obtained are shown in Table 1. The data in Table 1 show that CQDs-PTA-200 has a high content of N and S synergistic doping, and high content of N and S synergistic doping is the key to achieving high quantum yield, especially high content of sulfur forms bonds in the framework of CQD, which increases the quantum yield of carbon quantum dots.

[0041] Table 1 Element content of carbon quantum dots

[0042]

[0043] 3.3 FT-IR spectra of five nitrogen-sulfur co-doped carbon quantum dots CQDs-WAT-200, CQDs-FOA-200, CQDs-LAA-200, CQDs-PRA-200 and CQDs-PTA-200 are shown in the attached figure. Figure 2 The attached figure shows that the FIIR spectra of the above five CQDs are basically similar. The four CQDs under the DES system all contain six similar stretching vibration peaks (functional groups): -1 -OH / NH -1 , 2954cm -1 CH at 1700-1750cm -1 C=O at 1460cm -1 , C=C,1250cm -1 CO at 1031cm -1SO3 stretching vibration bands at the left and right. This shows that N and S atoms have been successfully doped onto the surface of CQDs. Furthermore, the C=O shift at 1700-1750cm-1 of the nitrogen-sulfur co-doped fluorescent carbon quantum dots CQDs-PTA-200 prepared by the present invention leads to the delocalization of π electrons in CQDs, resulting in changes in electron density, which in turn causes changes in the electronic structure of CQDs, thereby further improving the quantum yield of CQDs. Secondly, the -OH / NH-1 at 3300-3345cm-1 is compared with the CQDs intensity in the deionized water system. This doping preparation process may be accompanied by the formation of hydrogen bonds, which further changes the electronic structure of CQDs, all of which are attributed to the change in quantum yield caused by heteroatom doping. Again, the vibration peak at 1000-1450cm-1 is caused by SO3 and sulfide, and the vibration peak at around 600cm-1 is caused by the CS bond. With the increase of S content, the vibration peak at 1000-1450cm-1 becomes stronger and stronger, and the vibration peak caused by the CS bond reaches the maximum in the ChCl / PTA system, proving that high-content N and S synergistic doping is the key to achieving high quantum yield, especially high-content sulfur forms bonds in the framework of CQD, which can increase the quantum yield of carbon quantum dots.

[0044] 3.4 The XPS results of five nitrogen-sulfur doped carbon quantum dots CQDs-WAT-200, CQDs-FOA-200, CQDs-LAA-200, CQDs-PRA-200 and CQDs-PTA-200 are shown in Figure 3, (a) is the full spectrum, (b) is the fine spectrum. From the full spectrum of XPS, it can be seen that the peak positions of Na 1s, O 1s, N 1s, C 1s and S2p appear at around 1080ev, around 520ev, around 400ev, around 295ev and around 170eV respectively. The FIIR spectrum is further proved. The elements are further finely characterized. The C1s of each CQDs sample contains four peaks, which are related to the functional groups of C═C / C─C (about 284.5eV), C─N / C─O (about 250-288eV) and carboxylic acid O─C=O (about 289.8eV); N1s contains two peaks, corresponding to NH (about 399ev) and CN (about 402ev); O1s band shows two peaks, namely CO (about 533.2eV) and C=O (about 533.2eV); for S2p band, the sample has -C-SOx (x represents the number of S and O combined) at 164-169eV, which are SO3 / 2P3 / 2 and SO3 / 2P1 / 2, respectively, and <164ev is the peak position of metal sulfide. High-resolution XPS further proves that CQDs are functionalized with nitrogen and sulfur atoms, making the surface of CQDs rich in hydrophilic groups (-OH, -COOH, -NH2, etc.), which is conducive to the formation of multi-carbon rings, and also creates conditions for the formation of abundant surface defects in CQDs and the provision of heteroatom doping sites, thereby improving the fluorescence quantum yield. Crucially, the XPS spectrum shows that the total sulfur content is mainly composed of thiophene S and sulfone S, which means that thiophene S and sulfone S are successfully doped into the framework and edge functional groups of carbon quantum dots, and the high sulfur content of the carbon quantum dots in the ChCl / PTA system causes more carbon dot structural defects in the carbon dots, thereby changing the structure and energy level, and further improving the quantum yield of the carbon dots.

[0045] 3.5 UV-visible absorption spectra of five nitrogen-sulfur doped carbon quantum dots CQDs-WAT-200, CQDs-FOA-200, CQDs-LAA-200, CQDs-PRA-200 and CQDs-PTA-200 are shown in Figure 4 . Figure 4It shows that the trends of CQDs in different solvents are basically the same, and they all show two different absorption bands. CQDs-FOA-200, CQDs-LAA-200, CQDs-PRA-200, and CQDs-PTA-200 have strong absorption peaks around 210nm-220nm, which can be attributed to the π→π* transition of aromatic sp. It is worth noting that the CQDs prepared under the four DES systems are accompanied by a slight red shift, which can be attributed to the fact that CQDs-LAA-200 contains more graphitic carbon content. The CQDs prepared under the four DES systems have a medium-strong peak at 250nm-300nm, which can be attributed to the n→π* transition of C=O. It can be inferred that the CQDs prepared in this article contain rich conjugated structures. It is further proved that heteroatoms will increase the quantum yield of CQDs. Furthermore, the fluorescence spectra of five nitrogen-sulfur doped carbon quantum dots CQDs-WAT-200, CQDs-FOA-200, CQDs-LAA-200, CQDs-PRA-200 and CQDs-PTA-200 are shown in Figure 5 . Figure 5 It shows that when the excitation wavelength increases from 250nm to 270nm, the fluorescence intensity gradually increases, accompanied by a blue shift; when the excitation wavelength increases from 270nm to 310nm, the fluorescence intensity gradually decreases, accompanied by a red shift, indicating that carbon quantum dots are excitation-dependent. Different wavelengths of ultraviolet light excitation can produce fluorescence of different wavelengths. Figure 5 It shows that under ultraviolet light irradiation, CQDs-PTA-200 has the best fluorescence intensity and the corresponding quantum yield is the largest.

[0046] 3.6 The Raman spectrum of nitrogen-sulfur co-doped fluorescent carbon quantum dots CQDs-PTA-200 prepared by the present invention is shown in Figure 6 As can be seen from the figure, carbon quantum dots 1400cm -1 D peak (carbonization defect) appears around 1580cm -1 The G peak (carbonization degree) appears on the left and right, and the intensity ratio of the G peak to the D peak indicates the graphitization degree of the carbon quantum dots. The higher the graphitization degree, the better the application performance of CQDs. The I G / I D =1.42, while the I G / I DThey are 0.89, 1.08, and 1.33, respectively, indicating that the degree of graphitization from CQDs-FOA-200 to CQDs-PTA-200 is increasing, that is, the sp2 conjugated domain of CQDs is increasing, which is consistent with the characterization results of TEM and XRD. The p-toluenesulfonic acid provided by the present invention can more effectively change the degree of graphitization of CQDs, and the carbon quantum dots CQDs-PTA-200 formed therefrom have a highly ordered graphitized structure, thereby achieving an increase in particle size and adjustable red-shifted emission.

[0047] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing nitrogen-sulfur co-doped fluorescent carbon quantum dots with high quantum yield, characterized in that: Sodium lignin sulfonate is dissolved in a low eutectic solvent composed of choline chloride ChCl and p-toluenesulfonic acid PTA, and the reaction is heated to generate nitrogen-sulfur co-doped fluorescent carbon quantum dots N,S-CQDs after the reaction is completed; the low eutectic solvent composed of choline chloride ChCl and p-toluenesulfonic acid PTA is a low eutectic solvent ChCl / PTA composed of choline chloride ChCl and p-toluenesulfonic acid PTA in a molar ratio of 1:

1.

2. The preparation method according to claim 1, characterized in that The deep eutectic solvent contains 20% (m / v) sodium lignin sulfonate.

3. The preparation method according to claim 1, characterized in that: The heating reaction time is 14 hours, and the heating reaction temperature is 200°C.

4. The preparation method according to claim 1, characterized in that: After the reaction is completed, the reaction solution is cooled, and then the reaction solution is filtered, the filtrate is dialyzed, and finally the liquid in the dialysis bag is freeze-dried.

5. The preparation method according to claim 4, characterized in that: The filtration is carried out by using a 0.22 μm filter membrane; the filtrate is dialyzed in a dialysis bag for 48 hours, and the molecular weight cutoff of the dialysis bag is 1000.

6. The preparation method according to claim 1, characterized in that: The preparation method of the low eutectic solvent ChCl / PTA is as follows: a hydrogen bond acceptor choline chloride ChCl and a hydrogen bond donor p-toluenesulfonic acid PTA are mixed in a molar ratio of 1:1, the mixture is evenly mixed, and then heated and stirred to a clear and transparent liquid, and then cooled to room temperature to obtain a low eutectic solvent, which is recorded as ChCl / PTA.

7. Nitrogen-sulfur co-doped fluorescent carbon quantum dots N,S-CQDs prepared by the preparation method according to any one of claims 1 to 6.